Determining the performance of explosives for blasting management (Rudarsko-geološko-naftni zbornik, 2023)
Experimental methods for determining a performance index of explosives are analysed: the methods of a ballistic pendulum, ballistic mortar, a lead block, and according to the volume of soil explosion funnel. It is defined that the determination of a performance index of emulsion explosives (EE) involves a set of significant features connected with a large critical diameter requiring the experiments with large-mass charges and resulting in refusal from the traditional methods of determining a performance index. Analytical methods for calculating an index of relative performance of explosives are analysed. Determination of the performance indices of explosives with the help of analytical methods helps identify considerable differences in the calculation results; in case of emulsion explosives the results are erroneously low at all. It is since analytical methods do not consider the brisant action of emulsion explosives. This paper represents the developed methodology of determining a performance index of explosives according to the degree of detonation velocity. The proposed methodology considers the key energy and detonation characteristics of explosives: heat and volume of the explosion products, density (thickness), and detonation velocity. The use of analytical methodology for calculating a performance index for all explosive types makes it possible to get correct results that are necessary for designing the parameters of drilling and blasting operations.